Autism spectrum disorders: the complete guide to understanding autism, Asperger's syndrome, pervasive developmental disorder, and other ASDs - Sicile-Kira, Chantal (New York : Perigee Book, 2004)
Autism
Keywords: Popular works; Popular works. -- Asperger's syndrome; Popular works. -- Autism in children